2013
DOI: 10.3389/fmicb.2013.00165
|View full text |Cite
|
Sign up to set email alerts
|

A genetic system for Citrus Tristeza Virus using the non-natural host Nicotiana benthamiana: an update

Abstract: In nature Citrus tristeza virus (CTV), genus Closterovirus, infects only the phloem cells of species of Citrus and related genera. Finding that the CTV T36 strain replicated in Nicotiana benthamiana (NB) protoplasts and produced normal virions allowed development of the first genetic system based on protoplast transfection with RNA transcribed from a full-genome cDNA clone, a laborious and uncertain system requiring several months for each experiment. We developed a more efficient system based on agroinfiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In retrospect, allowing me to continue the project at that stage was both remarkably generous and far-sighted. Improvements in TLP purification, including (i) the finding that young bark of only certain citrus species is the best source of TLP, (ii) the use of a careful extraction procedure and precipitation of TLP using polyethylene glycol, and (iii) the use of different combinations of buffers for extraction and resuspension allowed us to obtain sufficiently purified TLP particles to establish their viral-like composition and biophysical nature (Bar-Joseph et al, 1972 ), the infectivity of which was demonstrated by Garnsey et al ( 1977 ).…”
mentioning
confidence: 99%
“…In retrospect, allowing me to continue the project at that stage was both remarkably generous and far-sighted. Improvements in TLP purification, including (i) the finding that young bark of only certain citrus species is the best source of TLP, (ii) the use of a careful extraction procedure and precipitation of TLP using polyethylene glycol, and (iii) the use of different combinations of buffers for extraction and resuspension allowed us to obtain sufficiently purified TLP particles to establish their viral-like composition and biophysical nature (Bar-Joseph et al, 1972 ), the infectivity of which was demonstrated by Garnsey et al ( 1977 ).…”
mentioning
confidence: 99%
“…Agroinoculation of citrus trees to obtain infection with different CTV expression vectors was found to be difficult. Thus, to avoid this difficulty, inoculation of citrus plants was carried out by stem-slashing or bark flap inoculation into 1-1.5-year-old Citrus macrophylla seedlings (68, 84) using virions purified from infected N. benthamiana plants (85,86). Direct agroinoculation of young leaves with citrus leaf blotch virus full-length cDNA clones was successful but only on Etrog citron (87); therefore, the virus species, virus construct, Agrobacterium strain, and host genotype all contribute to the success rate of agroinoculation.…”
Section: Alternative Inoculation Methods: Biolistics/vascular Puncture/agroinoculation/insectsmentioning
confidence: 99%
“…Currently, agroinfectious clones are available for eight closterovirids, the closteroviruses beet yellows virus (BYV) ( Prokhnevsky et al, 2002 ), citrus tristeza virus (CTV) ( Gowda et al, 2005 ; Ambrós et al, 2011 , 2013 ), and grapevine leafroll-associated virus 2 (GLRaV-2) ( Liu et al, 2009 ; Kurth et al, 2012 ), the criniviruses lettuce infectious yellows virus (LIYV) ( Wang et al, 2009 ), lettuce chlorosis virus (LCV) ( Chen et al, 2012 ), ToCV ( Orílio et al, 2014 ; Zhao et al, 2016 ), and cucurbit chlorotic yellows virus (CCYV) ( Shi et al, 2016 ), and the ampelovirus grapevine leafroll-associated virus 3 (GLRaV-3) ( Jarugula et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%